Pengenalan Dunia Teknik Sipil Bagi Siswa/I Smkn 1 Gunungsitoli: Pendekatan Edukasi Interaktif Dalam Sosialisasi Prodi - Zalukhu, Muhammad Haris; Daeli, Serta Denius; Giawa, Jun Fajar Krisman; Halawa, Ignasia Hastuti; Lase, Carsa Alim; Zebua, Friski Dermawan (CV. SINAR HOWUHOWU, 2025)
Early introduction to civil engineering is essential to enhance students' understanding and interest in this field. This study analyzes the effectiveness of an interactive education approach in the promotion of the civil engineering study program for students at SMK Negeri 1 Gunungsitoli. A mixed-methods research approach with a quasi-experimental design was used. The results showed that students who participated in interactive education-based promotion experienced a more significant increase in understanding and interest compared to those who received conventional methods. This approach proved to be more effective in increasing student engagement, providing more practical learning experiences, and helping them grasp civil engineering concepts more comprehensively. Therefore, an interactive education approach is recommended for study program promotion in vocational schools to enhance learning effectiveness and better prepare students for careers in civil engineering.